The Cyborg A Treatise on the Artificial Man - Caronia, Antonio (meson press, 2015)
Born on the pages of science fiction comics in the 1920s and 30s, the cyborg lives in popular imagination. As hero of the cyberpunk epic, in its brief but intense history, the cyborg has followed and anticipated the rapport and conflict between man and machine. In the post-fordist era of digital networked media the cyborg unfolds itself in the dissemination of multiple bodies: on the Internet, in the shift of individual identity, in the new collective aggregation connected by software. It bridges virtuality and concreteness, possibility and necessity. The cyborg thus becomes a field of social conflict, one of the new figures in which the bio-political perspective is embodied.